Pelestarian Warisan Seni Disabilitas: Studi Kasus dan Strategi Studio Tab Space Bandung - Sri Mulyati, Evi; Cahyana, Agus; Miftahul Falah, Asep; Roos Nagara, Martien (Universitas Sultan Ageng Tirtayasa, 2024)
The research conducted has the main objective of understanding how this social organisation contributes to the preservation and development of disability art, as well as identifying and analysing what strategies are used by Studio Tab Space in preserving and uplifting disability art. The researcher will also document the various initiatives taken by Studio Tab Space located in Bandung in order to maintain and develop the artistic heritage created by individuals with disabilities. Through a qualitative case study with an ethnographic approach, the researcher conducted a series of participatory observations and in-depth interviews with members of the social organisation, as well as collecting valuable data from documentation of activities. The results showed that Studio Tab Space Bandung has successfully created a space for disabled artists to express themselves and develop their skills. They use various strategies, such as training, performance, and collaboration with other non-disabled artists. This research contributes to the development of knowledge in the field of art by highlighting the importance of disability art preservation and the role of social organisations in this process.